Molecular identification of phlebotomine sand flies and the harbored Leishmania spp. in Sokoto State, Nigeria - Usman, Mahmud; Natala, Audu Joseph; Jatau, Isa Danladi; Ogo, Ndudim Isaac; Jeelani, Ghulam; Goto, Yasuyuki; Nozaki, Tomoyoshi; McKerrow, James H.; Balogun, Emmanuel Oluwadare (Frontiers in Cellular and Infection Microbiology, 2023)
Female sand flies are hematophagous, feeding on animals and in the process serve as vectors for Leishmania, the parasites that cause leishmaniasis in humans. Leishmaniasis are a group of parasitic neglected tropical diseases in 98 countries including Nigeria and kills 60,000 people/year. In Nigeria, Sokoto State is endemic to leishmaniasis but there is a knowledge gap on the identity of the prevalent sand flies and the Leishmania species they transmit. Hence, this crosssectional study was designed to take inventory of the species of sand flies in Sokoto using genetic methods. 1260 (310 females) sand flies were collected from three Local Government Areas (L.G.A) of Sokoto state-Wamakko, Sokoto south and Kware. Genomic DNA was extracted from each fly and DNA amplification by polymerase chain reaction (PCR) was carried out on the DNA samples using primers targeting the arthropods mitochondrial cytochrome oxidase subunit 1 (mt-coI) gene, and nested PCR with primers targeting the gene for Leishmania internal transcribed spacer-1 (its-1) of ribosomal RNA its-1rRNA. Gene sequence analysis revealed five species of sand flies belonging to the old-world genera namely Phlebotomus and Sergentomyia. The identified species were P. papatasi (6.45%), S. adleri (6.45%), S. affinis (9.7%), S. distincta (9.7%), S. schwetzi (67.7%). Within the sampling period, sand flies were most abundant in the rainy months of August (104/33.5%) and September (116/37.4%) with all the five identified species occurring. Sequence analysis of its-1 gene identified Leishmania infantum in two sand flies (2/310)-P. papatasi (from Sokoto South) and S. affinis (from Wamakko). BLAST search in NCBI and phylogenetic analysis revealed that the sand fly species are related to the species reported in different parts of Africa, while the L. infantum is identical to strain reported in Brazil (KY379083.1). In conclusion, Phlebotomus papatasi and four species belonging to the genus Sergentomyia are the most prevalent sand flies in Sokoto state, Nigeria and they harbour L. infantum solely. Therefore, our results shed light on why visceral leishmaniasis is the most predominant form of the disease and advise that adequate care for dogs must be instituted as dogs are the major animal reservoir for L. infantum.